Inflammatory reprogramming of alveolar macrophages by the bacterial peptide iE-DAP via PEPT2 transport - Masashi Kawami; Yutaka Takeuchi; Kosuke Fuji; Ryoko Yumoto; Mikihisa Takano; Yasuo Uchida (Toxicological Research, 2026)

Acute effects of flossing band application on hamstring muscle mechanical properties and stretch tolerance: a randomized controlled crossover trial - Gakuto Nakao; Ginji Nara; Yu Kondo; Risa Adachi; Koki Ishiyama; Keita Sekiguchi; Junpei Sawano; Shota Hirayama; Kotoka Kida; Masatoshi Nakamura; Kosuke Takeuchi; Masaki Katayose; et al. (European Journal of Applied Physiology, 2026)

QTN detection and candidate gene identification for improved eating and cooking quality in rice using GWAS and PLS regression analysis - Kiyosumi Hori; Matthew Shenton; Kenta Mochizuki; Keitaro Suzuki; Ken Iijima; Noriyuki Kuya; Koka Shu; Kosuke Ono; Yuji Kinoshita; Kazuhiko Sugimoto; Takayuki Umemoto; Jun-ichi Yonemaru; et al. (Theoretical and Applied Genetics, 2025)

Effects of training of shadowing and reading aloud of second language on working memory and neural systems - Hikaru Takeuchi; Tsukasa Maruyama; Yasuyuki Taki; Kosuke Motoki; Hyeonjeong Jeong; Yuka Kotozaki; Takamitsu Shinada; Seishu Nakagawa; Rui Nouchi; Kunio Iizuka; Ryoichi Yokoyama; Yuki Yamamoto; et al. (Brain Imaging and Behavior, 2021)
Shadowing and reading aloud both involve multiple complex cognitive processes, and both are considered effective methods for second-language learning. The working memory system, particularly the phonological loop, has been suggested to be involved in shadowing and reading aloud. The purpose of this study was to investigate the effects of a 4-week intensive adaptive training including shadowing and reading aloud of second language on working-memory capacity, regional gray matter volume (rGMV), and functional activation related to the n-back working-memory task in young adults. The results showed that compared with the training groups without speaking (listening to compressed speech and active control involving the second language), the training groups with speaking (shadowing and reading aloud) showed a tendency for greater test-retest increases in digit-span scores, and significantly greater test-retest decreases in N-back task reaction time (increase in working memory performance). Imaging analyses revealed compared with the active control group, shadowing group exhibited decreases in rGMV and brain activity during the working memory task (2-back task), in the left cerebellum and reading group exhibited decreases in them in the right anterior insula. These regions are parts of the phonological loop, suggesting the presence of training-induced neural plasticity in these neurocognitive mechanisms.

Copper chaperone antioxidant-1, Atox-1, is involved in the induction of SOD3 in THP-1 cells - Tetsuro Kamiya; Kosuke Takeuchi; Saki Fukudome; Hirokazu Hara; Tetsuo Adachi (BioMetals, 2018)